Theoretical Analysis On The Electrical Performance Of Long Coaxial Cable At Different Temperature - Kanisin, Devaraj (2006)

(untitled)
Long coaxial cables are widely used in telecommunication industry and, in oil and gas industry. The telecommunication industry mainly uses these cables for telecommunication between island, countries, etc. While in Oil and Gas Industry, the long coaxial cable plays a central role in production and well maintenance services. The long coaxial cable is attached with the down-hole monitoring equipment and travels to the well of 6 to 7 kilometres depth without repeaters. It is used to supply power to down-hole equipment and also provide communication link with the computer located at the oil rig or ship. During the transmission period, the long coaxial cable is often subjected to temperature differences and external noise interference. Both elements can be considered as interrelated with address to the degradation on the performance of the long coaxial cable. Therefore, the aim of the research is to investigate the performance of the long coaxial cable. The objectives are to analyze and evaluate the performance of the long coaxial cable corresponding to temperature differences, and also to develop and analyze the thermal transfer analysis for long coaxial cable. The methodology used for the research consists of five main stages such as mathematical analysis, designing long coaxial channel model as FIR filter, theoretical analysis, practical analysis and thermal transfer modeling. The study and the investigation were conducted on the MATLAB by designing a long coaxial channel model. The designed long coaxial model were experimented and analyzed for various length (eg:- 1 km, 3 km, 5 km, 6.096 km which equivalent to 20k feet, 8 km and 10km), various frequencies (eg: 10kHz, 50kHz and 100kHz) and various temperatures (eg: 20°C and 150°C). The experiment was repeated by considering the skin effect. Finally, the thermal transfer formula for the long coaxial cable is formulated and the same experiment above was repeated. In overall, the analysis shows the developed long coaxial channel model has the ability to evaluate and analyze the performance of any long coaxial cable at different temperatures leading to thermal transfer. Conclusively, four internal factors or criteria leading to thermal transfer have been identified, which plays the major role on the performance of the long coaxial cable at different temperatures. They are frequency, temperature, skin effect and length of the long coaxial cable.